Religious and Political Satire: An Analysis of some Arab Satiric poets (Eurasian Journal of Humanities and Social Sciences, 2023)
The aim of this study is to trace the reflection of the cultural elements in the poetry of some major Arab poets of satire, and the way the difference in periods and cultures affects the subjects and methods of satire. The Arab poets chosen are: AlHutay'ah (?), Al-Farazdaq (c. 20- c. 114 A.H.; c. 641- c. 732 A.D.), Jarir (c. 33- c. 114 A.H.; c. 653- c. 732 A.D.), Al-Akhtal (c. 20- 92 A.H.; c. 641- c. 710 A.D.), Bashar Ibn Burd (96- 168 A.H.; 714-784 A.D.), and Ibn ul-Rumi (221- 284 A.H.; 835-897 A.D.).